Sazonalidade da concentração de CO2 atmosférico em uma área agrícola no RS - Bevilacqua, Leticia Borges (2012)
In this work an agricultural area in Cruz Alta/RS was used to evaluate the seasonality of CO2 concentration with respect to meteorological variables of temperature, global radiation and rainfall. The study period was January 2009 to February 2011. In this period occurred the rotation of croups: soybeans-oats- soybeans-corn. The CO2 concentration date ware obtained by an infrared gas analyzer installed in a micrometeorological tower in the center of the agricultural area. The meteorological variables were obtained form a station INMET approximately 400m of the study area. The monthly average maximum CO2 concentration occurred in May 2010, and minimum in December 2009. The month of January and June of each year were used for a detailed analysis of the relationship between atmospheric CO2 concentration ant meteorological variables. Through the daily and monthly average concentration of CO2, can be said that an annual seasonality and interanual variability exist and that it is closely linked to the regime of precipitation, air temperature and global radiation. Assessing inter-annual variability is concluded that there is an evolution of the mean CO2 concentration throughout the study period.